ANALYSIS OF THE EFFECTIVENESS OF INSURANCE POLICY GUARANTEES BY THE DEPOSIT INSURANCE CORPORATION (LPS) IN INCREASING POLICYHOLDER PROTECTION IN INDONESIA - Selvi Santri; Syafriadi Syafriadi; Anisa Dwi Malik (Yayasan Pendidikan Islam Almatani, 2025)
This study was conducted to review the effectiveness of the Policy Guarantee Institution by the Deposit Insurance Corporation. The addition of the authority of the Deposit Insurance Corporation based on Law No. 4 of 2023 can cause problems. The consolidation of policy guarantee authority to the Deposit Insurance Corporation, which previously only guaranteed banking customers in accordance with Law No. 24 of 2004 concerning the Deposit Insurance Corporation, has an impact on the ineffectiveness in carrying out its duties. The purpose of this study is to determine how the policy guarantee institution is regulated in insurance companies in Indonesia and secondly, how effective the policy guarantee carried out by the Deposit Insurance Corporation. The method used in this study is normative juridical with a statutory regulatory approach. The results of this study indicate that the regulation of the Policy Guarantee Institution does not exist even though it has been mandated in Law Number 40 of 2014 concerning Insurance. The absence of regulations related to the Policy Guarantee Institution in insurance companies in Indonesia results in ineffectiveness and public distrust of insurance companies, so that regulations related to the Policy Guarantee Institution in insurance companies in Indonesia are needed.